Environmental & architectural phenomenology. Vol. 15, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2004)
Vol. 15, No. 3, Fall 2004 (includes “items of interest,” “citations received,” reviews of Douglas Rae's City and Jeff Malpas' Place and Experience, and essay by Bruce Janz).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals